A tribo Astereae Cass. (Asteraceae) no complexo de serras da Bocaina-Carrancas e Ouro Grosso – Minas Gerais - Ribeiro, William dos Santos (2017)
The Astereae tribe is the second largest tribe in the Asteraceae family and is widely distributed worldwide. In Brazil the tribe is represented by 16 genera and 208 species and 21 varieties, of which 178 species belong to the genus Baccharis, and presents a great diversity in physiognomies of rock field of Minas Gerais. The present work had as objective to carry out the taxonomic treatment of the tribe Astereae for the complex of Bocaina-Carrancas and OuroGrosso mountain ranges – MG, based on this and previous floristic surveys. Field trips from August 2105 to July 2016 were carried out in areas of natural remnants of rock field in the above mentioned area. Based on previous floristic surveys in the area, about 32 species of the tribe of these, 21 belonging to the genus Baccharis, three in Inulopsis and one in Conyza. In the present treatment, 23 species belonging to the tribe were identified, being 17 in Baccharis, two in Conyza, three Inulopsis and one in Leptostelma. Of these, three species: Baccharis calvescens, Baccharis helychrisoides and Leptostelma maximum, had not been reported in any of the cited works. Even with the area of study showing rupestrian fields disjoint and very close to anthropic regions, when compared to other rock areas of Minas Gerais, it can be considered the second largest center of diversity of the Astereae tribe for the state.